Idiopathic Pulmonary Fibrosis Associated with Pulmonary Hypertension: A Case Report on Diagnostic Challenges and Follow-Up Recommendations (International Journal of Scientific Research and Management (IJSRM), 2025)
Background: Idiopathic Pulmonary Fibrosis (IPF) is an insidious continuous interstitial lung disease presenting histologically with fibrous deposition, and the linings of alveolar sac in the lungs leading to respiratory failure. Pulmonary hypertension (PH) is one complication of IPF that often exacerbates symptoms and worsens prognosis. The association between IPF and PH still necessitates improved diagnostic approaches and tailored treatment approaches. Case Presentation: A 60-year-old male presented with complaints of severe dyspnea of severe dyspnea, tiredness, and orthopnea. Objective examination showed acrocyanosis, JVP elevation, and loud P2. On the chest radiograph and HRCT of the lungs, showed interstitial infiltrates with honeycombing and traction bronchiolectasis, which confirmed IPF. Echocardiogram and right heart catheterization confirmed PH, with the mean pulmonary arterial pressure recording at 45mmHg, while lung function tests showed decreased FVC, TLC and DLCO. Outcome: The patient was initiated on antifibrotic therapy, pirfenidone and pulmonary vasodilator (sildenafil). Over a six-month period, patient showed improvements in exercise capacity, dyspnea, and oxygenation. Prompt recognition and individualized treatment approach is needed in patient with pulmonary hypertension (PH) and idiopathic pulmonary fibrosis (IPF) progress. Conclusion: The patient herein highlights the importance of early identification and intervention of PH in IPF patients. A multidisciplinary approach with vasodilators and antifibrotic therapy are needed to improve symptoms, slow disease progression and improving on quality of life.